Framework Logbook Monitoring Aset Peralatan Operasional Berbasis Blockchain untuk Optimalisasi Manajemen Aset - Nardi Nardi; Mochamad Rifki Rismawan (Universitas Methodist Indonesia, 2025)
All equipment installed at BMKG Technical Implementation Units must be monitored in accordance with BMKG Head Regulation No. 7 of 2014. BMKG provides a web-based monitoring system called WebSIKI and a tunneling system to the BMKG Central network via VPN. However, these systems have been abandoned, and the current monitoring system at the South Tangerang Climatology Station UPT uses WhatsApp messages, email, and Google Spreadsheets to exchange data between agencies. The purpose of this research is to design a blockchain system to be implemented in the operational equipment monitoring system. The blockchain system will record monitoring data blocks and connect each previous monitoring data block that is related. The blockchain system is designed with the Hyperledger Fabric framework, the backend system is designed with Node.js using Hyperledger Fabric SDK for Node.js, and the frontend system is designed with React.js. This system was tested using the white box testing method to test the structural chaincode and black box testing to test the functionality of the system. The results of the structural and functional implementation and testing of the system show that the blockchain system is functioning properly and that the blockchain system can improve the security and integrity of equipment monitoring data.